MODELS AND ALGORITHMS FOR DETERMINING THE MULTIPLE FAILURES IN COMPLEX SYSTEMS - Litvinenko , A. E. (Problems of Informatization and Management, 2021)
Logical-linguistic models for determining multiple failures in complex systems are presented. A procedure for forming a system of algebraic inequalities is described, to the solution of which the problem of diagnostics is reduced on the basis of the above models. An algorithm for solving the problem of diagnostics, which implements the strategy of directed enumeration of options, is presented.